Qualitative data analysis : a methods sourcebook - Miles, Matthew B.; Huberman, A. M.; Saldana, Johnny (SAGE Publications, 2014)
Miles and Huberman's seminal text has helped thousands of graduate students and researchers find meaning from their qualitative data. New to this edition is the integration of qualitative analysis software, coverage of new approaches of inquiry, inclusion of mixed methods, and examples from a wider range of social science disciplines